Evidence based teledentistry: a systematic review of literature on smartphone apps - Datta, Shubham; Batra, Panchali; Raza, Uqba; Premchandani, Shubhangi; Sybil, Deborah (International Journal of Advances in Medicine, 2021)
Dental healthcare continues to be limited for large populations of both developing and developed nations. Hectic metropolitan work schedule, improper dentist-population ratio, lack of awareness, or global health emergencies such as the ongoing COVID-19 pandemic could be the possible reasons. This results in proliferation of teledentistry based practice, aided by global smartphone networking. Smartphone teledentistry apps require proper scientific literature backup along with ready availability in popular app stores such as Google Play store, and Apple app store. This article aims to identify which smartphone apps designed to provide teledentistry features are rooted in evidence-based literature such that the percentage of scientifically supported apps that were commercially available to consumers can be determined. Smartphone apps for teledentistry were evaluated in three phases. Phase 1 identified all teledentistry apps reported in the scientific literature. Phase 2 identified which apps from the literature review were available in the app stores. Phase 3 identified the top teledentistry apps available in the app stores. 11 studies identified 5 apps with only 1 being available in both the app stores. Few apps qualified the scientific searching process, whereas the number of apps available on app stores are greater.